2017
DOI: 10.1177/1469066717737904
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bio-oil produced by hydrothermal liquefaction of food waste using ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Recent research has revealed that more than 1.3 billion tons of food is wasted globally every year. The disposal of such huge biomass has become a challenge. In the present paper, we report the production of the bio-oil by hydrothermal liquefaction of three classes of food waste: meat, cheese and fruits. The highest yield of the bio-oil was observed for meat (∼60%) and cheese (∼75%), while for fruits, it was considerably low (∼10%). The molecular composition of the obtained bio-oil was investigated using ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Structural analysis of functional groups in bio-oils can be obtained by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy [6,20,21]. Analogously, Fourier transform infrared spectroscopy (FT-IR) has been used to determine the functional groups present in bio-oils constituents [10,[22][23][24][25]. Hence, spectroscopic techniques provide structural insight for the whole bio-oils compositions and are best suited to analyse changes in the functional group composition as a result of different upgrading processes.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analysis of functional groups in bio-oils can be obtained by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy [6,20,21]. Analogously, Fourier transform infrared spectroscopy (FT-IR) has been used to determine the functional groups present in bio-oils constituents [10,[22][23][24][25]. Hence, spectroscopic techniques provide structural insight for the whole bio-oils compositions and are best suited to analyse changes in the functional group composition as a result of different upgrading processes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the analysis the LTQ FT was calibrated using the standard thermo calibration mixture. For each peak in the peak list the following variables were calculated: [38][39][40][41][42] Results and discussion HTL results…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The results revealed a maximum oil content (16.8%) which could be used as bio‐oil (Sakuragi et al, 2016). Kostyukevich et al reported a high yield (75%) of bio‐oil from cheese waste by hydrothermal liquefaction (Kostyukevich et al, 2017). Mohamed, 2018 reported (0.25 g/g) heavy bio‐oil yield from corn sticks through liquefaction.…”
Section: Bio‐oilmentioning
confidence: 99%